Effect of methanol concentration on the performance of asymmetric cellulose acetate reverse osmosis membranes using dry/ wet phase inversion technique - Idris, A.; Ismail, A. F.; Iswandi, S.; Shilton, S. J. (Penerbit UTM Press, 2001)
Asymmetric membranes were prepared from a multicomponent dope polymer solution consisting of cellulose acetate, acetone, formamide and methanol. In this work, the drybet phase inversion technique is used and the presence of methanol is studied. In addition, this work also presents the fundamental issues involved in altering flat sheet casting solutions to produce solutions, potentially useful for preparing hollow fibers within, defect free selective layers. Variations in the composition of multicomponent casting solution resulted in membranes with drastically different reverse osmosis performance. The membrane performance are determined experimentally by primary parameters such as the pure water permeation rate (PWP), salt permeation rate (PR) and rejection rates. From these da@ the secondary parameters such as pure water permeability constant (A), solute transport parameter (DAM/K6) and mass kansfer coefficient (k) are determined. These parameters are important in the prediction of reverse osmosis performance and also in characterising membrane morphology. ?he results revealed that the presence of methanol in the dope formulation increases the percentage of salt rejection and flux flow. The relatively laver value of (DAM/K6) for a reference solute indicates a relatively smaller average pore size on the membrane surface.